2001
DOI: 10.1016/s0736-5748(01)00052-1
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the effects of prenatal gamma irradiation on the dorsal lateral geniculate nucleus of Swiss mice

Abstract: A previous study reported that adult mice irradiated at the 16th embryonic day present a severe neuronal number reduction in the dorsal lateral geniculate thalamic nucleus. In the present study, we investigated the time course of the effects of prenatal irradiation on this thalamic nucleus. One day after irradiation, a great number of pyknotic figures were seen mainly in the cerebral proliferative zones. In the geniculate nucleus, only scattered pyknotic figures were identified. On the first week after birth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Other researchers have suggested that cortical neurons will die later in development following prenatal irradiation due to a lack of sufficient synaptic connections (76). Additionally, nerve growth factor (NGF) production in mouse neurons has been shown to be reduced following irradiation (77). Because radiation interferes with the processes regulating normal cell death, exposure may induce apoptosis in neurons that would not have otherwise been removed from the growing brain and our underlying assumption may not be valid.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers have suggested that cortical neurons will die later in development following prenatal irradiation due to a lack of sufficient synaptic connections (76). Additionally, nerve growth factor (NGF) production in mouse neurons has been shown to be reduced following irradiation (77). Because radiation interferes with the processes regulating normal cell death, exposure may induce apoptosis in neurons that would not have otherwise been removed from the growing brain and our underlying assumption may not be valid.…”
Section: Discussionmentioning
confidence: 93%